Entropy and Non-Equilibrium Statistical Mechanics - Scarfone, Antonio M.; Abe, Sumiyoshi; Kovács, Róbert (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nonequilibrium statistical mechanics has a long history featuring diverse aspects. It has been a major research field in physics and will remain so in the future. Even regarding the concept of entropy, there exists a longstanding problem concerning its definition for a system in a state far from equilibrium. In this Special Issue, we offered the possibility to discuss and present up-to-date problems that were not necessarily restricted to statistical mechanics. Theoretical and experimental papers are both presented, in addition to unifying research works. As the entropy itself is the central element of nonequilibrium processes, papers discuss various formulations of the second law and its consequences. In this Special Issue, recent progress in kinetic approaches to hydrodynamics, rational extended thermodynamics, entropy in a strongly nonequilibrium stationary state, and related topics are reported as both review articles as well as original research works.